The Khidmah Tradition of Santri Towards Kyai (The Review of ‘Urf & Psychology) - Aufa Abdillah; Erkham Maskuri (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
The tradition of khidmah Santri to Kyai is a tradition in Pondok Pesantren that has coexisted since the beginning of the spread of Islam and is preserved up to now in the recent millennial era. Many ordinary people do not understand the tradition of khidmah Santri to Kyai and consider it such a